2021
DOI: 10.3390/su13158394
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Portfolio System (APS) Usage Intention of Senior High School Students in Taiwan

Abstract: Taiwan began to implement a new high school syllabus nationwide, in 2019. The Ministry of Education has also established a high school student Academic Portfolio System (APS) to collect the learning process of high school students for future university admissions references. However, during this period, high school students and their parents had many opinions on the implementation of the new system. There were even groups of students protesting. The main purpose of this research is to explore the factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(75 reference statements)
0
2
0
1
Order By: Relevance
“…The theoretical foundation of this research is the Technology Acceptance Model (TAM), which was first developed to investigate how new technology adoption occurs [16], [17]. The Theory of Reasoned Action (TRA), which focuses on how individuals assess the value and benefits of blockchain technology, forms the basis of this model [18], [19]. Usability-related aspects are used to measure the extent to which the new technology can improve student performance, while ease-of-use aspects are used to evaluate how accessible the technology is.…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical foundation of this research is the Technology Acceptance Model (TAM), which was first developed to investigate how new technology adoption occurs [16], [17]. The Theory of Reasoned Action (TRA), which focuses on how individuals assess the value and benefits of blockchain technology, forms the basis of this model [18], [19]. Usability-related aspects are used to measure the extent to which the new technology can improve student performance, while ease-of-use aspects are used to evaluate how accessible the technology is.…”
Section: Methodsmentioning
confidence: 99%
“…Amron et al reported the mediating effect of perceived usefulness and perceived ease of use as relevantly positive in understanding why people would accept cloud computing (Amron et al, 2022). Accordingly, TAM also magnifies its successfulness in 10 predicting users' adoption in many research contexts such as teachers acceptance on new powerful educational tools (Masril et al, 2021), or predicting the usage of APS on senior high school students in Taiwan (Chang & Chiu, 2021), examining the acceptance of learning management system (Stockless, 2018), and further investigation on technology acceptance on mathematics teachers in Turkey (Gurer, 2021). All studies highlighted TAM's predictive power on user's acceptance on technology.…”
Section: Perceived Usefulness and Perceived Ease Of Usementioning
confidence: 99%
“…A TRA define que o comportamento do indivíduo é determinado por sua intenção comportamental, ou seja, as relações entre crenças, atitudes, normas, intenções e comportamentos dos indivíduos. Essa intenção, por sua vez, é determinada por atitudes e normas subjetivas de cada pessoa em Evento online www.even3.com.br/cobicet2023 relação ao comportamento (AJZEN, 1991a;CHANG, TSEN-YAO;CHIU, 2021). A TPB modifica o modelo anterior com a inclusão de um terceiro elemento, gerando um modelo em que a intenção comportamental encontra expressão no comportamento, desde que o comportamento em questão estiver sob controle da força de vontade, ou seja, quem decide em executar o comportamento é o indivíduo (AJZEN, 1991b;BUABENG-ANDOH, 2021;NGAFEESON;GAUTAM, 2021b).…”
Section: Theory Of Planned Behavior (Tpb) é a Evolução Daunclassified